PENGARUH STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA (EARNINGS MANAGEMENT) (CONFLICT AGENCY TYPE 1) PADA PERUSAHAAN YANG LISTING DI BEI - Razelia Keishari Agita Sembiring; Vince Ratnawati; Al Azhar L Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to investigate the effect of managerial ownerships, institutional ownerships and public ownerships components to earnings management on the companies that listed in Indonesian Stock Exchange. Data is used in this research is secondary data from monetary data in Indonesian Stock Exchange. The sample method used was purposive sampling. From the all of companies listed in the Indonesian Stock Exchange, research sample counted 80 companies that meet criteria. Hypothesis testing is done by using multiple linear regression analysis.The result of this research based on hypothesis test show that managerial ownerships does not have significant effect with earnings management, while institutional ownerships and public ownerships have significant effect with earnings management. The magnitude of the effect (Adj R-Square) of managerial ownerships, institutional ownerships, and public ownerships on earnings management was 1,6%. While the remaining 98,4% is influenced by other variables.Keywords: managerial ownerships, institutional ownerships, public ownerships, earnings management.